2018
DOI: 10.1021/acs.est.8b04848
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout Maintain Intestinal Transport and Barrier Functions Following Exposure to Polystyrene Microplastics

Abstract: Ingestion has been proposed as a prominent exposure route for plastic debris in aquatic organisms, including fish. While the consequences of ingestion of large plastic litter are mostly understood, the impacts resulting from ingestion of microplastics (MPs) are largely unknown. We designed a study that aimed to assess impacts of MPs on fish intestinal physiology and examined integrity of extrinsic, physical and immunological barriers. Rainbow trout were exposed to polystyrene (PS) MPs (100–400 μm) via feed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 78 publications
4
24
1
1
Order By: Relevance
“…Regarding progressive changes, in our study, the number and size of goblet cells did not show significant differences among the test groups. Likewise, a study conducted on Onchorhyncus mykiss fed PS MPs showed no significant changes in the numbers of goblet cells observed 58 . Although prior studies 95,118 have mentioned mucous hypersecretion, none of the photomicrographs provided showed a significant presence of mucous secretion.…”
Section: Histopathological Changesmentioning
confidence: 90%
See 2 more Smart Citations
“…Regarding progressive changes, in our study, the number and size of goblet cells did not show significant differences among the test groups. Likewise, a study conducted on Onchorhyncus mykiss fed PS MPs showed no significant changes in the numbers of goblet cells observed 58 . Although prior studies 95,118 have mentioned mucous hypersecretion, none of the photomicrographs provided showed a significant presence of mucous secretion.…”
Section: Histopathological Changesmentioning
confidence: 90%
“…In contrast, Asmonaitè et al . found limited impacts on gut integrity in Oncorhynchus mykiss exposed to MP particles for 4 weeks 58 . Jovanovic et al .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…An important general phenomenon to note is that toxicological responses typically arise from smaller plastic particles. Larger PS particles at around 100 µm or above were shown not to have any significant effect in a number of studies [65][66][67]. MP/NP feeding can result in behavioral abnormalities in terms of feeding and movement of adults and larvae [35,[68][69][70][71][72][73][74], as well as reproduction in adults [75][76][77].…”
Section: Introductionmentioning
confidence: 98%
“…Estos resultados contrastan a los obtenidos previamente por Alomar et al (2017), quienes no obtuvieron evidencia del estrés oxidativo y daño celular en el hígado de M. surmuletus; sin embargo, también visualizaron el aumento de la enzima GST, lo que sugiere la inducción del sistema de detoxificación del pez. Esta falta de evidencia podría sustentarse según Ašmonait et al (2018), quienes emplearon a Oncorhynchus mykiss «trucha arcoiris» para estudiar los efectos de los microplásticos tras un periodo de ingesta de 4 semanas, sin embargo, los resultados obtenidos no pudieron detectar ningún efecto significativo sobre la barrera intestinal, por lo cual concluyeron que los efectos nocivos de los microplásticos en peces dependen de su especie y el periodo de exposición.…”
Section: Resultados Y Discusiónunclassified